Analysis of diclofenac in water samples using in situ derivatization-vortex-assisted liquid-liquid microextraction with gas chromatography-mass spectrometry - Aydin Senar; Aydin Mehmet Emin; Beduk Fatma; Tekinay Arzu; Kilic Havva (Acta Pharmaceutica)
A novel micro-extraction technique for a rapid and sensitive analysis of diclofenac (DCF) in water samples has been developed. DCF was derivatized and extracted simultaneously using vortex-assisted liquid-liquid micro-extraction (VALLME) prior to gas chromatography with mass spectrometry detection. The effects of extraction solvent volume, extraction and derivatization time and ionic strength of the sample were studied using 23 factorial experimental design. The optimum extraction conditions were as follows: 200 μL of chloroform, 25 μL of N-methyl-N-trimethylsilyl-trifluoroacetamide (MSTFA) derivatization reagent, vortex extraction and derivatization time 5 min at 3000 rpm. The extraction recovery for different fortification levels was 98 %. Also, the proposed micro-extraction method exhibited results comparable with the solid phase extraction of real water samples. The proposed one-step VALLME and derivatization method is simpler and faster than the conventional extraction and derivatization methods used for the determination of DCF in real water samples.